Calibration of Traffic Incident Simulation Models Using Field Data - Rompis, Semuel; Habtemichael, Filmon (http://dx.doi.org/10.31427/IJSTT.2019.2.1.3, 2019)
This study presents a methodology to calibrate a traffic incident simulation model, particularly in a freeway. The queue length was used as the objective of the simulation model calibration in this study. The simulation model was set up using Traffic Simulation Model PTV. VISSIM. Multiple incident durations were simulated, and the generated queue lengths were compared to the observed queue lengths. The observed queue lengths were estimated using the LWR model and shockwave speeds calculated using the field data. The results confirm that calibrated VISSIM incident model can signify the shockwave propagation speeds and queue length in the event of freeway incident. Such a model can be implemented as an instrument for setting up traffic management strategies to alleviate the incident’s impact.